Inaccuracies in the computational procedures of acquiring composite laminate’s plastic deformation with the forward Euler algorithm - Ren, Rui (Composite structures, 2018)
Several inaccuracies in one published paper about predicting laminate’s transverse impact nonlinear behaviors with an elasto-plastic damage model are presented. Plastic strain rates obeying the associative flow rule are suggested to be modified. Computational procedures concerning about the solution of yielding function for updating plastic strain with the forward Euler algorithm are also reformulated. And possible explanations about reasonably updating the proportionality factor within the initial zero equivalent plastic strains are expected. This contribution aims at improving and completing the proposed computational procedures of predicting polymer based composite material’s plastic deformation with the forward Euler algorithm.